Design of Selective Leakage Protection Circuit Based on Method of Amplitude Discrimination and Phase Discriminatio - FAN Yi-long~; LI Hang~; YOU Guo-dong~ (Gong-kuang zidonghua, 2010)
The paper proposed a design scheme of selective leakage protection circuit based on method of amplitude discrimination and phase discrimination for electrical control equipments of fully mechanized devices of coal mine underground.The selective leakage protection circuit applied the principle that the phase of zero-sequence current in fault line is in contrast to the one in non-fault line and the phase of zero-sequence current delays the phase of zero-sequence voltage in fault line.It realized function of selective leakage protection for electrical control equipments of fully mechanized devices of coal mine underground through comparison of phases of zero-sequence current and zero-sequence voltage as well as their amplitudes and the setted amplitude.The practice showed that the circuit has strong adaption ability,flexible application,and good reliability.